Acupuncture as an Independent or Adjuvant Management to Standard Care for Perimenopausal Depression: A Systematic Review and Meta-Analysis - Zhao, Fei-Yi; Fu, Qiang-Qiang; Kennedy, Gerard A.; Conduit, Russell; Zhang, Wen-Jing; Zheng, Zhen (Frontiers in Psychiatry, 2021)
Background Many women with perimenopausal depression (PMD) have sought alternative therapies such as acupuncture because of concerns about risks associated with antidepressant and hormone replacement therapy (HRT). This systematic review aimed to clarify if acupuncture is effective for PMD compared with waitlist control or placebo-/sham-acupuncture, and if acupuncture alone or combined with standard care (antidepressant and/or HRT) is more effective in ameliorating PMD in comparison to standard care alone. Methods Randomized controlled trials (RCTs) of PMD treatment via acupuncture Vs. waitlist-control or placebo-/sham-acupuncture, and RCTs of PMD treatment via acupuncture alone or combined with Western pharmacotherapy Vs. Western pharmacotherapy were searched for from seven databases from inception to December 2020. Cochrane criteria were followed. Results Twenty five studies involving 2213 women were analyzed. Meta-analyses indicated that acupuncture significantly reduced the global scores of Hamilton Depression Scale (HAMD) [SMD= -0.54, 95%CI (-0.91, -0.16), p< 0.01], compared with standard care. The therapeutic effect of acupuncture maintained at 2-week, 4-week and 12-week follow-ups. Acupuncture combined with standard care was more effective than standard care alone in decreasing HAMD scores [SMD= -0.82, 95%CI (-1.07, -0.58), p< 0.01]. Too few RCTs were available to assess the clinical efficacy differences between acupuncture and placebo-/sham-acupuncture or HRT alone. Acupuncture also showed better effects in decreasing Kupperman Index (KI) scores, whether compared with antidepressant alone [MD= -4.55, 95%CI (-8.46, -0.65), p= 0.02] or antidepressant combined with HRT [MD= -0.89, 95%CI (-1.34, -0.43), p< 0.01]. Conclusions In comparison to standard care, acupuncture alone or combined with standard care was associated with significant improvements in PMD, and reductions of other menopausal symptoms. This finding suggests that acupuncture may be a useful addition to treatment for PMD.